Bleeding Jejunal Diverticulosis in a Patient with Myasthenia Gravis. (11th March 2008) - Zuber-Jerger, I.; Endlicher, E.; Kullmann, F.
Abstract : A seventy-year-old male presented with severe myasthenia gravis and an episode of obscure bleeding. There was a history of gastric ulcer leading to Billroth II surgery twenty-five years ago. Upper endoscopy revealed no pathology. Colonoscopy showed a few solitary diverticula and traces of old blood in the terminal ileum. Capsule endoscopy pictured red smear in the upper jejunum. Diverticula were seen as well. Suspecting bleeding jejunal diverticulosis double balloon enteroscopy was performed. The complete jejunal ascending loop and about 100 cm of the jejunum through the descending jejunal loop could be inspected. Large diverticula with fecoliths were found in both loops. Bleeding had ceased. The patient was discharged to neurology for optimizing therapy for myasthenia gravis.